Flower palate ultrastructure of the carnivorous plant Genlisea hispidula Stapf with remarks on the structure and function of the palate in the subgenus Genlisea (Lentibulariaceae) - Płachno, Bartosz J.; Świątek, Piotr; Stpiczyńska, Małgorzata; Miranda, Vitor Fernandes Oliveira [UNESP] (Springer Nature, 2018)
In the genus Genlisea as well as in its sister genus Utricularia, the palate probably plays a key role in providing the colour, mechanical and olfactory stimuli to attract insect pollinators and to guide them to the generative structures and the nectary spur. However, information about the micro-morphology of the palate of Genlisea is scarce. This study aims to examine the structure of the palate in Genlisea hispidula in detail as well as the palate from other five species from the subgenus Genlisea. In particular, its aim is to ascertain whether these palates function as an area for the osmophores in the flower or whether they produce nectar. We showed that the palate in all of the species that were examined was the glandular type and that it had capitate, glandular trichomes, which had a similar general architecture across the species that were examined. No nectar secretion was observed on the palates. The ultrastructure of the palate trichomes showed that the palate glandular trichomes most probably function as scent glands that produce an olfactory stimulus for flower pollinators.
Keywords: Bladderwort; Carnivorous plant; Corkscrew plants; Floral micro-morphology; Genlisea; Glands; Lamiales; Lentibulariaceae; Osmophore; Pollination; Trichome; Ultrastructure; Utricularia